PENGEMBANGAN BAHAN AJAR BERBASIS CERITA FIKSI DALAM PEMBELAJARAN TEMATIK SUBTEMA MANFAAT TUMBUHAN BAGI KEHIDUPAN MANUSIA KELAS III DI SD - Henjulaspan Dekajuang Nyimpado; Siti Halidjah; Asmayani Salimi (Universitas Tanjungpura, 2022)
AbstractThis study aims to produce teaching materials based on fiction by raising the sub-theme of the benefits of plants for human life for third grade students at SDN 13 Lonjengan in the form of printed textbooks and pdf documents with a file size of 4.4 MB and contains the main material of the 2013 curriculum for semester 1 class. three with the theme 2 loving plants and animals Sub-theme 1 the benefits of plants for human life have met the basic competencies, indicators, and learning objectives and are appropriate according to the assessment of media experts, material experts, teachers and students. The feasibility of teaching materials is based on the assessment of experts, the average percentage from the media aspect is 4.2 with very decent criteria, and 5.0 from the material aspect it has very decent criteria. The feasibility of teaching materials in the first phase of the trial was based on responses from teachers with an average percentage of 4.9 having very decent criteria, and 4.4 of students having very decent criteria. In the second stage of the trial, based on the teacher's response to the use of teaching materials, 5.0 criteria were very feasible, and 4.56 student assessments had very decent criteria.Keywords: Development, Teaching Materials, Fiction Stories